Kolomiyets L. V. Gregory Corso’s allusive phrases and their «second life» as names and quotations from the vantage point of translation - Kolomiyets L. V. (Philological Treatises, 2020)
The article discusses the possibilities of conveying in translation Gregory Corso’s allusive surrealistic word combinations from his poem «Marriage» in the context of their contemporary usage in fictitious names and quotations. The prerequisite of translating allusive poetry lies in an intensive pre-translational study of the ST associative matter while taking into consideration additional associative connections engendered by independent usage of ST fragments in made-up titles, quotations, and personal names. Translating the Beatniks’ poetry should be truthful, informative, and lead to the author’s allusions and associations, eschewing their naïve literal and perfunctory dictionary interpretation.